PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA LINGKUNGAN ASISTEN PEMERINTAHAN DAN KESEJAHTERAAN RAKYAT DI SEKRETARIAT DAERAH KOTA - yanto heryanto (Jurnal Ilmiah Publika, 2013)
The title of this study is "The Effect of Motivation and Discipline Working on Employee Performance in Government Asisiten Environment and Social Welfare Secretariat in Cirebon. Study aims to analyze (1) the efect of work motivation and discipline on employee performance and Welfare Administration Assistant in the Regional Secretariat Cirebon, (2) the efect of motivation on employee performance and Welfare Administration Assistant at Regional Secretariat Cirebon, and (3) the efect of labor discipline on employee performance and Welfare Administration Assistant at Regional Secretariat Cirebon.The research method used is descriptive explanative (explanatory descriptive) and that the sample in this study is the staff of the Assistant Government and Social Welfare Regional Secretariat Cirebon. The collection of primary data obtained through interviews and questionnaires using questionnaires, and secondary data obtained from the agency that has to do with the study. The resulting data were analyzed by descriptive statistics and, using path analysis (Path analisys).The results showed that : (1) motivation and discipline together significantly affect employee performance and Welfare Administration Assistant Regional Secretariat Cirebon. The results obtained hypothesized path coefficients motivation affects employee performance by 13,00%, the coefficient of labor discipline pathways affect the performance of employees at 34,10%, or the influence of motivation and work discipline cumulative effect on employee performance by 47,10%. That is the kind of motivation and discipline of work, the better the performance of employees in performing their duties and functions, (2) significant motivation on employee performance and Welfare Administration Assistant Regional Secretariat Cirebon. The results obtained path coefficients motivation hypothesis directly affect the performance of employees by 6.30% and an indirect relationship of 6,70%, thus determining the total motivation employee performance by 13,00%. This means that the better the motivation, the better the performance of employees in performing their duties and functions, and (3) labor discipline significantly affect employee performance and Welfare Administration Assistant Regional Secretariat Cirebon. The results obtained path coefficients discipline hypothesis directly affect the work performance of employees amounted to 27.40% and indirect relationships by 6.70%, so the total variable labor discipline determine employee performance by 34,10%. That is the kind of employee discipline, the better the performance of the employee in carrying out its duties and functions.